Utility of augmented breast self-examination as an education and screening tool in Rural India for early detection of breast cancer - Suresh, A. V. S.; Sharma, Rakesh; Dattatreya, P. S.; Vamsy, C. Mohana (International Journal Of Community Medicine And Public Health, 2021)
Background: Breast cancer contributes 19-34%, the percentages vary according to the region. There is an immense need for the structured breast cancer screening, which should start with education of breast self-examination (BSE). However due to poor literacy and education, we thought of augmenting the same (aBSC) with use of hand held device across various camps and compared with clinical breast examination (CBE) and conducting feasibility study. Methods: Data from screening camps between 2018-2020 using standardized AV tools (15 minutes duration) were analysed followed by a question answer section to elicit the understanding with 20:1 random check. For BSE and a aBSE we did verification for the understanding and adoption of techniques as per instruction manual. The participants were observed and supervised by trained personal during the process followed by CBE. The results BSE, aBSE and CBE were documented. Results: We trained 7214 women 2018-2020. Of the total trained persons, 93.8% of women understood accurately. aBSE was done for 1085. Comparison was done between the aBSC and CBE. aBSE could detect 92.6% of all the lumps identified by CBE, which is much better than 68% of BSE. There are 23.4% more suspicious lumps were unearthed after aBSE after conventional BSE. Of all the camps we detected 356 new lumps and malignancies were confirmed in 142 participants, which indicated high impact of such training programs in Rural India. Conclusions: BSE and aBSE are quite useful in clinical detection of lump and is easy to implement. With detection rate of 1.9%, which is quite high especially in the rural areas where medical facilities are poor, we feel that aBSE can be adopted in large scale and is well accepted among rural women and can improve on conventional breast self-examination and is comparable with clinical breast examination.